Exploring Key Genes and Mechanisms in Respiratory Syncytial Virus-Infected BALB/c Mice via Multi-Organ Expression Profiles - He, Yu; Wang, Zhili; Wei, Jianhua; Yang, Zhongying; Ren, Luo; Deng, Yu; Chen, Shiyi; Zang, Na; Liu, Enmei (Frontiers in Cellular and Infection Microbiology, 2022)
Respiratory syncytial virus (RSV) can cause complications in multiple organs, thus increasing hospital stays and costs. However, RSV-based studies have primarily focused on effects in the lungs and blood, thereby potentially neglecting critical genes and pathways. Hence, studying RSV infection via a novel multi-organ approach is important. In this study, lung, intestine, brain, and spleen tissues from six BALB/c mice (6–8 weeks old; three in control group and three in RSV-infected group) were subjected to RNA sequencing. Differentially expressed genes (DEGs) in each organ were obtained and functional enrichment analysis was performed. We first used CIBERSORT to evaluate the immune-infiltration landscape. Subsequently, common DEGs (co-DEGs) among the four organs were analyzed to identify key genes and pathways. After quantitative reverse transcription-polymerase chain reaction, western blotting, and external validation analysis of key hub genes, their correlation with immune cells and potential functions were explored. We found that the host response to RSV infection varied among the four organs regarding gene expression profiles and immune cell infiltration. Analysis of the 16 co-DEGs indicated enrichment in the platelet and neutrophil degranulation pathways. Importantly, the key gene hemopexin (Hpx) was strongly correlated with the immune cell fraction in the lungs and may participate in the regulation of platelet activation and immune response.